![image](https://tex.z-dn.net/?f=%5Cint%7B%5Cfrac%7Bx%5E2dx%7D%7Bx%5E3-4%7D%7D%3D%5C%5C%0A%5C%7Cdx%5E3%3D3x%5E2dx%3D%3D%3Ex%5E2dx%3D%5Cfrac13dx%5E3%5C%7C%5C%5C%0A%3D%5Cint%7B%5Cfrac%7B%5Cfrac13dx%5E3%7D%7Bx%5E3-4%7D%7D%3D%5Cfrac13%5Cint%7B%5Cfrac%7Bdx%5E3%7D%7Bx%5E3-4%7D%7D%3D%5C%5C%0A%5C%7Cd%28x%5E3-4%29%3Ddx%5E3%5C%7C%0A%3D%5Cfrac13%5Cint%7B%5Cfrac%7Bd%28x%5E3-4%29%7D%7Bx%5E3-4%7D%7D%3D%5C%5C%0A%5C%7Cx%5E3-4%3Dp%3Bd%28x%5E3-4%29%3Ddp%5C%7C%5C%5C%0A%3D%5Cfrac13%5Cint%7B%5Cfrac%7Bdp%7D%7Bp%7D%7D%3D%5Cfrac13%5Ccdot%5Cln%7Cp%7C%2BC%3D%5Cfrac13%5Cln%7Cx%5E3-4%7C%2BC)
x^2dx=\frac13dx^3\|\\
=\int{\frac{\frac13dx^3}{x^3-4}}=\frac13\int{\frac{dx^3}{x^3-4}}=\\
\|d(x^3-4)=dx^3\|
=\frac13\int{\frac{d(x^3-4)}{x^3-4}}=\\
\|x^3-4=p;d(x^3-4)=dp\|\\
=\frac13\int{\frac{dp}{p}}=\frac13\cdot\ln|p|+C=\frac13\ln|x^3-4|+C" alt="\int{\frac{x^2dx}{x^3-4}}=\\
\|dx^3=3x^2dx==>x^2dx=\frac13dx^3\|\\
=\int{\frac{\frac13dx^3}{x^3-4}}=\frac13\int{\frac{dx^3}{x^3-4}}=\\
\|d(x^3-4)=dx^3\|
=\frac13\int{\frac{d(x^3-4)}{x^3-4}}=\\
\|x^3-4=p;d(x^3-4)=dp\|\\
=\frac13\int{\frac{dp}{p}}=\frac13\cdot\ln|p|+C=\frac13\ln|x^3-4|+C" align="absmiddle" class="latex-formula">